Analysis Of PVDF Membrane Incorporated With Graphene Oxide (GO) Performance For Oily Water Treatment - MOHAMED, NURUL AIN; Binti Misdan, Nurasyikin (Progress in Engineering Application and Technology, 2023)
Due to significant improvements in its intrinsic properties, particularly hydrophilicity and anti-fouling resistance, as well as low energy requirements and ease of operation, the microporous polymeric-based membrane has become increasingly used in a wide range of water treatment processes over the years. In general, ultrafiltration (UF) membranes with pore sizes between 0.01 and 0.1 m are considered sufficient for treating oil–water emulsions and producing high-quality permeate, but their low resistance to oil deposition and adsorption are likely to shorten the membrane’s lifespan, especially when dealing with high concentrations of oily wastewater. This study was aimed to investigate the potential of a Polyvinylidene fluoride (PVDF) membrane incorporated with the graphene oxide (GO). PVDF was chosen as the main polymer due to its anti-oxidation properties, high thermal stability, good organic selectivity as well as excellent chemical and mechanical resistances. The presence of GO was not only improved the hydrophilicity and water flux of the membrane, but also helped to reduce potential fouling problem [1]. The main research objectives were to fabricate PVDF membrane incorporated with GO by using NIPs method, to characterize the chemical and physical properties and to analyse the potential performance in oil rejection. The concentration of PVDF is 9 wt%, 12 wt% and 6 wt% while for GP was 0wt% and 0.1wt%. There are 3 different ratio of PVDF to PES solution which are 1:1, 2:1 and 1:2. Chemical properties of the prepared composite membrane will be characterize using contact angle (CA) and Fourier Transform Infrared (FTIR). Physical properties will be characterize using Scanning Electron Microscopic, (SEM) and Atomic force microscopy (AFM).The The best performance of the membrane for this study was the b(ii) membrane that has concentration PVDF to PES was 12 wt% to 6wt%. This contributed to the 2472.03 L/m2h and has 97.898 % in rejecting oil. For future study, industries should provide opportunities for researchers to test their treatment plants using industrial oily wastewater rather than laboratory oily wastewater.